2020
DOI: 10.1177/1938640019897224
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Addition to Popliteal Nerve Blocks: Effects on Duration of Analgesia and Incidence of Postoperative Nerve Complication

Abstract: Background. The purpose of this prospective, double-blinded randomized control pilot study was to evaluate the effect of adjunctive dexamethasone on analgesia duration and the incidence of postoperative neuropathic complication. Peripheral nerve blocks are an effective adjunct to decrease postoperative pain in foot and ankle surgery, and any possible modalities to augment their efficacy is of clinical utility. Methods. Patients were randomly assigned to a control group (n = 25) receiving nerve blocks of bupiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Gagne et al [ 36 ] demonstrated that nerve injury was more likely to persist without full recovery in the perineural dexamethasone group than in the ropivacaine-only group (47.65% vs. 32.41%); nevertheless, this study was retrospective, and the nerve injury rates were inconceivably high. Noori et al [ 37 ] reported that 10% of patients experienced neuropathic complications 1year after popliteal block, and there was no difference between the dexamethasone group and the placebo group. In our study, we found a similar incidence of sensory deficit among the three groups at 6 months after surgery (12%,16% and 8%), yet our sample size was relatively small and not large enough to elucidate the differences in the safety profiles between the two routes of dexamethasone; thus, studies including larger patient samples are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Gagne et al [ 36 ] demonstrated that nerve injury was more likely to persist without full recovery in the perineural dexamethasone group than in the ropivacaine-only group (47.65% vs. 32.41%); nevertheless, this study was retrospective, and the nerve injury rates were inconceivably high. Noori et al [ 37 ] reported that 10% of patients experienced neuropathic complications 1year after popliteal block, and there was no difference between the dexamethasone group and the placebo group. In our study, we found a similar incidence of sensory deficit among the three groups at 6 months after surgery (12%,16% and 8%), yet our sample size was relatively small and not large enough to elucidate the differences in the safety profiles between the two routes of dexamethasone; thus, studies including larger patient samples are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, postoperative nerve injury was not found in patients in either group 3 days after TKA. Current clinical studies have not yet found that the use of dexamethasone peripherally causes long-term neurological injury 35,36. In animal models, no nerve cell death was detected when dexamethasone was administered peripherally 37,38.…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical studies have not yet found that the use of dexamethasone peripherally causes long-term neurological injury. 35,36 In animal models, no nerve cell death was detected when dexamethasone was administered peripherally. 37,38 Therefore, cautious use was recommended by Baeriswyl et al 39 Further clinical observation and studies are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies assessed the rate of nerve injuries in PNBs done in total joint replacement, which showed incidences in the range of 0.5% to 5%. 1,2,14,26 Noori et al 18 recently conducted a prospective, randomized control pilot study looking at the effect of dexamethasone addition to PNB in foot and ankle surgeries on the duration of analgesia and the incidence of postoperative nerve complications. To our knowledge, this is the only other study that looked at the long-term incidence of nerve complications following popliteal block.…”
Section: Discussionmentioning
confidence: 99%